2008
DOI: 10.1136/jmg.2007.057174
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in the BRCA1 promoter influence transcription and are associated with decreased risk for breast cancer in Chinese women

Abstract: Background-The BRCA1 gene is an important breast cancer susceptibility gene. Promoter polymorphisms can alter the binding affinity of transcription factors, changing transcriptional activity and may affect susceptibility to disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…Accumulating evidence also demonstrated that not only reduced DNA repair capacity due to polymorphisms in the coding region, but also decreased expression of DNA repair genes resulting from genetic polymorphisms in the regulatory region was associated with increased risk of human cancers [37][38][39][40][41]. The XRCC1 gene, which maps to chromosome 19q13.2 and consists of 17 exons, encodes a scaffold protein that interacts with most of the core components participated in the BER pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence also demonstrated that not only reduced DNA repair capacity due to polymorphisms in the coding region, but also decreased expression of DNA repair genes resulting from genetic polymorphisms in the regulatory region was associated with increased risk of human cancers [37][38][39][40][41]. The XRCC1 gene, which maps to chromosome 19q13.2 and consists of 17 exons, encodes a scaffold protein that interacts with most of the core components participated in the BER pathway.…”
Section: Discussionmentioning
confidence: 97%
“…In all these cases, the incorporation of the now 30+ common breast cancer susceptibility alleles into comprehensive risk prediction models will be of great value in allowing women and their providers to make informed management decisions. In addition, it would be interesting to specifically explore if BRCA1 haplotypes altering promoter activity,34 35 or potentially altering 3′ untranslated region (UTR) microRNA binding,36 influence the level of function of R1699Q in vivo, and explain in part the variable presentation of families.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Chan et al found that rs799906, located in the promoter region of BRCA1 gene, could increase promoter activity through altering the binding affinity of transcriptional factor. This study also concluded that rs799906 decreased breast cancer risk (OR = 0.72, 95%CI = 0.53-0.97, P = 0.032) by genotyping 380 cases and 390 controls recruited in Hong Kong [37]. Therefore, maybe rs799906 is the real causal variant.…”
Section: Commentmentioning
confidence: 84%